A state-wide study on perceptions towards intimate partner violence among young adults attending premarital courses - Wan Soliha Wan Mohd Hanafi,; Tengku Alina Tengku Ismail,; Anis Kausar Ghazali,; Zaharah Sulaiman,; Aziah Daud, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Intimate partner violence (IPV) is a global health issue. Limited knowledge exists about IPV among young adults as they are in a critical period of transition to adulthood and encounter serious dating and partnerships. This study sought to determine the perceptions and factors associated with perceptions towards forms of IPV. A total of 305 young adults with the mean age of 24 years old, were recruited from premarital courses in Kelantan, using a random sampling method. After obtaining their consent to participate, the participants responded to a self-administered validated questionnaire. Logistic regression analysis revealed that misperceptions towards physical violence are significantly associated with female and high income; misperceptions towards psychological violence associated with female, self-employed and high income, and while misperceptions towards controlling actions related to female and middle income. The results highlight that this issue may due to a lack of education and cultural gender role. There is a need for efforts to accurately target these factors through comprehensive prevention programs to address IPV in this population more effectively.